2015
DOI: 10.1007/s13594-015-0224-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between production conditions and milk gross composition in ewe’s and goat’s organic and conventional farms in central Greece

Abstract: Organic milk and dairy products are widely consumed lately, with the belief they are of higher nutritional quality than conventional, while researchers report contradictory views on this issue. This study aimed to compare the fat, protein, and lactose content of organic and conventional raw ewe's and goat's milk in Greece and to further associate the impact of the farming practices on these parameters. Two hundred thirty-four bulk milk samples were collected from 62 goat and 16 sheep organic and conventional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
(25 reference statements)
2
16
0
5
Order By: Relevance
“…The pasture in spring was found to contain higher amounts of MUFA and PUFA than the one in winter in various Mediterranean countries (Cabiddu et al, 2005). Seasonal variations of the fat content have been reported in previous studies for ovine milk (Prandiniet al, 2004;Carloni et al, 2010), bovine (Lu et al, 2018) or caprine milk (Malissiova et al, 2015). The supplementation of feeds with fish oil, which is rich in MUFA and PUFA, affected the lipogenic genes of mammary gland and decreased the fat content of the ovine milk (Carreño et al, 2016).…”
Section: Resultsmentioning
confidence: 66%
“…The pasture in spring was found to contain higher amounts of MUFA and PUFA than the one in winter in various Mediterranean countries (Cabiddu et al, 2005). Seasonal variations of the fat content have been reported in previous studies for ovine milk (Prandiniet al, 2004;Carloni et al, 2010), bovine (Lu et al, 2018) or caprine milk (Malissiova et al, 2015). The supplementation of feeds with fish oil, which is rich in MUFA and PUFA, affected the lipogenic genes of mammary gland and decreased the fat content of the ovine milk (Carreño et al, 2016).…”
Section: Resultsmentioning
confidence: 66%
“…In Spain, a comparison between milk from organic and conventional systems showed significantly higher values of MUFA and PUFA, including cis ‐9, trans ‐11 CLA, while SFA decreased in milk . Additionally, two studies conducted in Greece on conventional or organic dairy sheep and goat farms showed either similar or lower fat content in the organic sheep and goat milk compared with the corresponding conventional milk. In addition, the organic milk from sheep had higher contents of MUFA, n‐3 PUFA and cis ‐9, trans ‐11 CLA whereas in organic goat milk 18:3n‐3 and n‐3 FA contents were higher than those of conventional milk .…”
Section: Effects Of Dietary Feedstuffs Rich In N‐3 Pufa On the Milk Lmentioning
confidence: 94%
“…Susu organik dapat berasal dari ternak ruminansia seperti sapi, kambing, domba dan kerbau yang dipelihara berdasarkan sistem peternakan organik (Di Francia et al 2007;Battaglini et al 2009;Miotello et al 2009;Tsiplakou et al 2010;Malissiova et al 2015). Kualitas susu organik, diantaranya kandungan gizi, masih menjadi perdebatan karena berdasarkan beberapa penelitian menunjukkan bahwa susu organik memiliki sedikit perbedaan dengan susu konvensional (Rosati & Aumaitre 2004;Sato et al 2005).…”
Section: Kualitas Susu Organikunclassified
“…Saat ini permintaan terhadap susu organik meningkat (Liu et al 2013;Malissiova et al 2015) dengan asumsi bahwa mengonsumsi susu yang berasal dari peternakan organik akan memberikan manfaat yang berbeda dibandingkan mengonsumsi susu dari peternakan konvensional (Malissiova et al 2015). Harga susu yang berasal dari peternakan organik lebih tinggi dari susu yang berasal dari peternakan konvensional, karena susu organik diproduksi dengan ramah lingkungan dari ternak yang tidak menggunakan antibiotika, hormon, bahan kimia sintetis, tanpa modifikasi genetik sehingga memiliki manfaat potensial bagi kesehatan manusia (Schwendel et al 2015).…”
unclassified